2018
DOI: 10.1155/2018/4203737
|View full text |Cite
|
Sign up to set email alerts
|

Altered Salivary Alpha-Amylase Secretion in Patients with Ulcerative Colitis

Abstract: Purpose Patients with ulcerative colitis (UC) frequently present with psychological disturbances as well as dysfunctions of autonomic nervous system (ANS). Salivary alpha-amylase (sAA) secretion is predominantly controlled by sympathetic nervous activity, while salivary fluid secretion is by parasympathetic nervous activity. Thus, it is speculated that alterations of salivary secretion may be addressed in UC populations. Methods Thirty-five UC patients as well as 32 age- and sex-matched healthy controls were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…This finding is consistent with the studies showing that the elevated salivaryalpha amylase level was associated with depression severity in the major depressive disorder patients [42,43]. According to other studies, elevated secretion of salivary-alpha amylase was associated with a higher prevalence of psychiatric disorders [15,27]. Thus, we suggested that salivary-alpha amylase activity was correlated with depression in T2DM patients with depression in this study.…”
Section: Plos Onesupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is consistent with the studies showing that the elevated salivaryalpha amylase level was associated with depression severity in the major depressive disorder patients [42,43]. According to other studies, elevated secretion of salivary-alpha amylase was associated with a higher prevalence of psychiatric disorders [15,27]. Thus, we suggested that salivary-alpha amylase activity was correlated with depression in T2DM patients with depression in this study.…”
Section: Plos Onesupporting
confidence: 93%
“…Participants were instructed not to eat, drink, or exercise before collection. To collect saliva samples, the passive drooling method was used [27]. Saliva was stored at −20˚C until the analysis of salivary-alpha amylase activity [27].…”
Section: The Assessment Of Salivary Alpha-amylase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The next diagnostic biomarker can be salivary α-amylase (sAA) described by Xu et al [ 27 ] in UC patients. According to the literature, this protein’s production positively correlates with the copy number of AMY1 gene [ 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, an increase in the concentration of alpha-amylase compared to healthy controls was observed in both the stimulated and unstimulated saliva of UC patients, although no significant changes were observed in the flow rates. Changes in alpha-amylase secretion were not associated with an increase in the number of copies of the gene responsible for alpha-amylase [ 55 ]. The authors of the latter study concluded that the elevated alpha-amylase secretion in UC patients might be due to the involvement of sympathetic overactivity in the UC population.…”
Section: Amylase and Mucin 5bmentioning
confidence: 99%